EFFECTIVENESS OF THE LACEY ASSESSMENT OF PRETERM INFANTS TO PREDICT NEUROMOTOR OUTCOMES FOR PREMATURE BABIES AT TWELVE MONTHS CORRECTED AGE (International Journal of Physiotherapy, 2020)
Background: The Lacey Assessment of Preterm Infants (LAPI) is used in clinical practice to identify premature babies at risk of neuromotor impairments, especially cerebral palsy. There is a shortage of studies on the Lacey assessment despite its wide clinical use. This study attempted to find the diagnostic accuracy of the Lacey assessment of preterm infants to predict neuromotor outcomes of premature babies at 12 months corrected age and to compare their predictive ability with brain ultrasound.Methods: This prospective cohort study included 89 preterm infants (45 females & 44 males) born below 35 weeks gestation. An initial assessment was done using the Lacey Assessment of Preterm Infants (LAPI) after babies reached 33 weeks postmenstrual age. Follow up assessment on neuromotor outcomes was done at 12 months (±1 week) corrected age using two standardized outcome measures, i.e., Infant Neurological International Battery and Alberta Infant Motor Scale. Brain ultrasound data were collected retrospectively. Data were statistically analyzed, and the diagnostic accuracy of the Lacey Assessment of Preterm Infants (LAPI) alone and in combination with brain ultrasound was calculated.Results: Fisher's exact test showed p